Edukasi Pemanfaatan Metode Vakum dalam Memperpanjang Masa Simpan Produk Pangan - Eka Andriani; Al Mukhlas Fikri; Qurratu Aini; Widya Astuti (Jurnal Abdimas ADPI Sains dan Teknologi, 2022)
Karawang Regency has quite high culinary business potential because apart from being an industrial area of ​​Karawang it is also a tourist area. Most Karawang residents have culinary businesses, especially in the form of street vendors, warteg, catfish penyet stalls, to restaurants. However, the products being sold are fresh food products that will quickly deteriorate. This service aims to assist culinary entrepreneurs in producing food products that have a longer shelf life during production and marketing. In addition, it is hoped that it can help culinary entrepreneurs maintain the nutritional value of the products to be sold and can provide added value in sales by utilizing vacuum packaging. Education is carried out for the people of Ciampel, Karawang Regency through demonstrations or demonstrating how to pack food ingredients using the vacuum method. The activities carried out were tested first at the Padjadjaran University Laboratory in Bandung to determine the nutrient content on the first day of packaging, the seventh day and the 14th day of packaging using samples of raw snakehead fish which were packaged using the vacuum method through 2 treatments, namely salted and without being sprinkled with salt. Laboratory results showed that samples with vacuum packaging covered with salt were still suitable for consumption on seven day.